THE EFFECT OF USING COGNITIVE STRATEGY INSTRUCTION (CSI) ON STUDENTS’ ACHIEVEMENT IN WRITING REPORT TEXT - Rizka Hayati; Tjut Ernidawati (Universitas Negeri Medan, 2015)
This study aims to discover the effect of applying Cognitive Strategy Instruction on students’ achievement in writing report text. It was conducted by using experimental research design. The population of this research was the eleventh (XI) grade students of SMA Negeri 4 Binjai. The samples of the research were two classes which consisted of experimental and control group which were chosen by using purposive technique. Thirty students were taken as the samples in each class. The experimental group was taught by using Cognitive Strategy Instruction, while the control group was taught without using Cognitive Strategy Instruction. After analyzing the data, it was found that the value of tobserved was 3,10 with the degree of freedom (df)=58 at the level of significance p(0,05) = 2,000. It means that tobserved was higher than ttable (3,10>2,000). The result of this study showed that Cognitive Strategy Instruction was significantly affect on students’ achievement in writing report text.